A DNA–Cu nanocluster and exonuclease I integrated label-free reporting system for CRISPR/Cas12a-based SARS-CoV-2 detection with minimized background signals. Issue 32 (13th July 2022) - Xie, Siying; Qin, Cheng; Zhao, Furong; Shang, Zhaoyang; Wang, Pei; Sohail, Muhammad; Zhang, Xing; Li, Bingzhi
Abstract : A fluorogenic reporter integrating a DNA–Cu nanocluster and Exo I was developed for CRISPR/Cas12a-based SARS-CoV-2 detection with minimized background signals. Abstract : CRISPR-driven biosensing is developing rapidly, but current studies mostly adopt dye-labeled ssDNA as the signal reporter, which is costly and unstable. Herein, we developed a label-free and low-background reporter for CRISPR/Cas12a signaling by integrating DNA-templated copper nanoclusters (DNA–CuNCs) and exonuclease I (EXO I). The template of the DNA–CuNCs was rationally designed as a ds-/ss-DNA hybrid, ensuring that after a quick and nonpersistent cut of Cas12a, a majority of the template can be digested by EXO I. Based on this novel reporter, a biosensor termed CRISPR-CNS (cost-effective, nimble, and sensitive copper nanocluster sensor integrating CRISPR) was developed. Due to the high signal-to-background ratio of our proposed reporter, CRISPR-CNS shows excellent performances for nucleic acid detection, yielding a detection limit of 20 copies for SARS-CoV-2 RNA. Considering its facile synthesis, robust fluorescence, effective cost, and good sensitivity, this combination shall serve as a highly potential output for CRISPR-based point-of-care testing.